2021
DOI: 10.3389/fpsyg.2021.753987
|View full text |Cite
|
Sign up to set email alerts
|

Motives for Studying and Student Wellbeing: Validation of the Motivational Mindset Model

Abstract: Research on the joint effect of multiple motives for studying was recently given a push in a new direction with the introduction of the motivational mindset model (MMM). This model contributes to a better understanding of study success and student wellbeing in higher education. The aim of the present study is to validate the newly developed model and the associated mindset classification tool (MCT). To this end, 662 first-year university students were classified in one of the four types of motivational mindset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…The self-impact mindset had a weaker sense of purpose than the high-impact and social-impact mindset, while these students reported equal feelings of engagement toward their studies as the social-impact mindset students. The low-impact mindset students revealed the least optimal pattern in the two student qualities: the weakest sense of purpose and lowest level of study engagement (Hudig et al, 2021).…”
Section: Motivational Mindset Modelmentioning
confidence: 95%
See 4 more Smart Citations
“…The self-impact mindset had a weaker sense of purpose than the high-impact and social-impact mindset, while these students reported equal feelings of engagement toward their studies as the social-impact mindset students. The low-impact mindset students revealed the least optimal pattern in the two student qualities: the weakest sense of purpose and lowest level of study engagement (Hudig et al, 2021).…”
Section: Motivational Mindset Modelmentioning
confidence: 95%
“…A follow-up study showed that sense of purpose and study engagement were meaningfully related to the motivational mindsets (Hudig et al, 2021). Both purpose and study engagement are central dimensions of wellbeing and important predictors of study success (Dahl et al, 2020;Martínez et al, 2019;Pizzolato et al, 2011;Widlund et al, 2018).…”
Section: Motivational Mindset Modelmentioning
confidence: 99%
See 3 more Smart Citations